Turkic-Speaking Population on the Steppe Borderland of the Grand Duchy of Lithuania and the Crimean Khanate in the 15th – the First Half of the 16th Centuries - Vladyslav V. Hrybovskyi (Lietuvos Istorijos Studijos)
The ethnic and demographic situation on the borderland of the Grand Duchy of Lithuania and the Crimean Khanates is analysed on the basis of narratives (Michalon Lituanus, Marcin Broniowski, Marcin Bielski, Bartosz Paprocki) and documentary sources (publications “Lithuanian Metrics”, “Archive of South Western Russia”, documents of the Russian State Archive of Ancient Acts, Central State Historical Archive of Ukraine).